2009
DOI: 10.1111/j.1365-2362.2009.02158.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of body fat mass extent on cardiac autonomic alterations in women

Abstract: Morbidly obese, normoglycaemic and normotensive young women have increased HR and low HRV, indicating an abnormal cardiac autonomic function and representing a risk factor for adverse cardiovascular events. A decrease of HRV parameters is associated with a progressive increase of body FM. Other metabolic and hormonal factors, characterising obesity, do not show an independent influence on these HRV alterations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
36
0
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 41 publications
7
36
0
4
Order By: Relevance
“…In fact, it has been shown that during sodium load, higher SSI is associated with higher HR and lower cardiac vagal modulation, 5 these relationships disappearing when shifting to a low sodium intake. Moreover, insulin resistance was found to be associated both with higher 24-hour HR levels 9 and with higher sodium sensitivity, 6,7 these data further highlighting the existence of a link between elevated HR and sodium sensitivity. In line with our hypothesis, we found a positive correlation between HR 24H and SSI (Table 3).…”
Section: Definition Of Sodium Sensitivity Risk From Map Nf and Hr 24hmentioning
confidence: 53%
See 2 more Smart Citations
“…In fact, it has been shown that during sodium load, higher SSI is associated with higher HR and lower cardiac vagal modulation, 5 these relationships disappearing when shifting to a low sodium intake. Moreover, insulin resistance was found to be associated both with higher 24-hour HR levels 9 and with higher sodium sensitivity, 6,7 these data further highlighting the existence of a link between elevated HR and sodium sensitivity. In line with our hypothesis, we found a positive correlation between HR 24H and SSI (Table 3).…”
Section: Definition Of Sodium Sensitivity Risk From Map Nf and Hr 24hmentioning
confidence: 53%
“…The HR cutoff was set at 70 bpm on the basis of the reported differences in HR 24H between subjects with and without metabolic syndrome. 9 These classification criteria, based on ABPM data only, allowed us to define 3 subgroups of patients in whom we hypothesize a different degree of sodium sensitivity: a group at low risk for sodium sensitivity (SSLR), including patients classified both as dippers and low HR at 24-hour ABPM; a group at high risk of sodium sensitivity (SSHR), including patients classified both as nondippers and high HR at ABPM; and a group at intermediate sodium sensitivity risk, including patients belonging neither to SSLR nor to SSHR groups because they were classified as dippers and high HR or as nondippers and low HR at ABPM.…”
Section: Classes Of Salt Sensitivity Risk From Abpmmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations were consistent with many others in which subjects with the metabolic syndrome, who are insulin resistant and SS, have increased sympathetic nervous system activity and heart rates. 39,[425][426][427] Another characteristic of many groups of hypertensive patients (eg, secondary hypertension, obstructive sleep apnea, chronic renal insufficiency) is a diminished sleep-associated reduction in BP (nondipping of BP), which is known to have detrimental prognostic implications. Subjects with features of the SS hypertensive phenotype such as the metabolic syndrome also have a high prevalence of nondipping.…”
Section: Surrogate Markers Of Ssbp In Humansmentioning
confidence: 99%
“…30 Similarly, individuals with higher BMI have been shown to have higher RHR, 31 potentially due to increased sympathetic nervous system activation. 32,33 Higher BMI has also been associated with a significantly increased odds for having CAC. 34 Because it seems more physiologically plausible that smoking and increased body mass result in a higher RHR (instead of vice-versa), and both of these variables were significantly associated with CAC in our study population, we believe smoking and BMI are confounders rather than downstream mediators of the association between RHR and CAC.…”
Section: Allison Et Almentioning
confidence: 99%